La traduction anglaise du Pastor fido de Guarini par Richard Fanshawe (1647) : quelques réflexions sur la naturalisation - Line Cottegnies (Etudes Epistémè)
This paper looks at the enduring popularity of Guarini’s Il Pastor fido  through the seventeenth century. It focusses more particularly on Richard Fanshawe’s 1647 translation, which superseded a 1602 anonymous translation and was to go through six editions by th end of the century. As will be apparent, its success is linked with its politics of naturalization. First, Fanshawe politicized the pastoral by using the paratext as a way of suggesting an allegorical, political reading of the play; but he also naturalized the work by adapting it for his Caroline readers. He translated it into the poetic idiom current at the time he was writing and turned it into a baroque work. This essay focusses on a few of the strategies of naturalization Fanshawe used to turn the work into a Cavalier pastoral which distanced itself from the very conventions of the genre. Paradoxically, it is this naturalization which could explain the endurance of the work: the Pastor fido might thus have been immortalized not as what it was, a late sixteenth-century pastoral drama, one of the first of the genre, but as a baroque, Caroline work — which would have appeared slightly outdated by 1660, but would still have had its appeal at the Restoration.